Evaluation of Credit Repayment Behaviour Among Farmers Multipurpose Cooperative Societies (Members) in Abia State, Nigeria (UNIZIK Journal of Agricultural Economics and Extension, 2024)
This study examined the credit repayment behaviour among farmers’ multipurpose cooperative members in Abia State Nigerian credit has been one of the critical inputs in agriculture, also regarded as an effective means of economic transformation and poverty alleviation. Credits affect the performance of agriculture by providing resources for the purchases of inputs and adoption of new technology. The study specifically examined the range of amount of credit applied amount approved, amount disbursed and amount repaid by the FMCS, to investigate socio-economic factors affecting the FMCS members’ credit repayment ability and ascertain major problems affecting FMCS members in credit repayment. T-test statistics and a multiple econometric model of the ordinary least square OLS) were used. The joint effect of the explanatory variable and model account for 91.9% of the variations in the factors affecting the FMCS member’s credit repayment ability. Four coefficients, educational qualification, farm size, credit application cost, collateral value are significant. Age, membership duration and income of members are not significant but they showed a positive relationship with credit repayment factors affecting the members credit repayment ability are significant 0.00 significant level. This study therefore, recommends among others the following; FMCS should endower to educate their members on financial discipline and management hence significantly influence credit repayment. Lending institutions should ensure that whoever they are lending needs a minimum threshold. This will help to reduce defaulting.
Keywords: Abia State; Cooperative societies; Credit repayment; Farmers